The waning of vision’s hegemony: A phenomenological perspective on mother-daughter discord in patriarchal societies - Lötter, Casper (The Indo-Pacific journal of phenomenology, 2021)
If phenomenology is a research methodology uniquely positioned to enable us to learn from others, I aim to demonstrate the idea that cinema is a privileged site from which to investigate the notion of virtuality (sight and reality), even in an age where vision’s predominance is waning. In order to do so, I consider the painfully disruptive mother-daughter relationship found cross-culturally and discourse-analytically in contemporary patriarchal societies. This bond is arguably of central concern to feminists (and women in general) since previous research has found that the fractious nature of this dynamic points to a very specific psychological deformation of the female psyche under conditions of sexist oppression. The views of French psychoanalyst and philosopher Julia Kristeva and other feminist contributors to the debate on this psychological construct are considered. The possibility of a cultural remedy inspired by a secularised trend of Chinese Buddhism in post-Maoist China, a society very different from that of the West, is investigated. This will involve the analysis of the film Curse of the Golden Flower (Chinese Mandarin soundtrack and English subtitles). I subsequently explore whether or not a valuable model for the compromised mother/daughter relationship is available within the context of the notion of a "slave economy" in the comparatively healthier mother/son relationship of (contemporary) Han Chinese culture. By means of cross-cultural analysis as research tool, this article finds confirmation for the proposition of a positive mother/daughter dynamic in the French novelist Colette’s relationship with her mother, Sido. In conclusion, I find that cinema (as an art form serving the eye, i.e. virtuality) is particularly well suited as a site to investigate psychological phenomena by way of interpretative phenomenology as a research methodology, even as vision - as the human sense of choice - has begun to wane amid a global crisis in masculinity.